1978
DOI: 10.1210/endo-103-6-2252
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Dietary Carbohydrate Content on Insulin Binding and Glucose Metabolism by Isolated Rat Adipocytes*

Abstract: The effects of changes in the amount of dietary carbohydrate (CHO) on cellular insulin and glucose metabolism have been assessed in rat adipocytes. Feeding animals a 67% CHO (fat-free) diet resulted in decreased insulin binding but enhanced activity of both the glucose transport system and intracellular pathways of glucose metabolism. Feeding rats a 67% fat (CHO-free) diet resulted in decreased insulin receptors as well as decreased activity of the glucose transport system and intracellular glucose metabolism.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
27
1

Year Published

1981
1981
1998
1998

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(33 citation statements)
references
References 44 publications
5
27
1
Order By: Relevance
“…Nonetheless, we believe that a more complete study of the range of doses over which the model is applicable would be worthwhile. is independent of acute changes in insulin it may be related to the influence of basal insulin concentration on the levels of those enzymes that are dependent upon a constant insulin environment for their activities, such as glucokinase and glycogen synthase in the liver (29,30) and glucose transport units in tissues for which glucose transport is insulin dependent (31). Thus, the diminished glucose effectiveness may be related to insulin resistance in that it could be a secondary manifestation of the resistance of tissues to the "permissive" rather than acute effects of the hormone.…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, we believe that a more complete study of the range of doses over which the model is applicable would be worthwhile. is independent of acute changes in insulin it may be related to the influence of basal insulin concentration on the levels of those enzymes that are dependent upon a constant insulin environment for their activities, such as glucokinase and glycogen synthase in the liver (29,30) and glucose transport units in tissues for which glucose transport is insulin dependent (31). Thus, the diminished glucose effectiveness may be related to insulin resistance in that it could be a secondary manifestation of the resistance of tissues to the "permissive" rather than acute effects of the hormone.…”
Section: Resultsmentioning
confidence: 99%
“…A higher carbohydrate content in the diet of rats may, after a longer time, reduce insulin binding by cells of this tissue and intensify intracellular degradation of the hormone. Despite this, the uptake of glucose by fat cells may by elevated (Olefsky and Seakow, 1978). Glucose is then converted to a greater degree to triglycerides (Olefsky and Seakow, 1978).…”
Section: Hormonal Regulationmentioning
confidence: 99%
“…Despite this, the uptake of glucose by fat cells may by elevated (Olefsky and Seakow, 1978). Glucose is then converted to a greater degree to triglycerides (Olefsky and Seakow, 1978). In experiments using fat cells from young pigs, it was shown that feeding these animals feeds with the addition of maize starch caused a distinct rise in lipogenesis stimulated by insulin (Smith et al, 1996).…”
Section: Hormonal Regulationmentioning
confidence: 99%
See 2 more Smart Citations